Dark tourism as educational tourism: the case of 'hope tourism' in Fukushima, Japan. Issue 4 (4th July 2021) - Jang, Kyungjae; Sakamoto, Kengo; Funck, Carolin
ABSTRACT: This article examines how dark tourism has been adopted and developed in Japan and suggests how it can be linked to educational tourism, through the case of a 'Hope Tourism Guided Tour' held in Fukushima in 2018. In Japan, dark tourism has developed into a new form, nested within educational tourism (or an educational tourism that contains elements of dark tourism within it). This is connected to the long history of educational tourism and to the cultural backlash against dark tourism. Hope tourism in Fukushima is an example of this type of new educational tourism-centred dark tourism. First, we review how the concepts of educational and dark tourism have spread in Japan. Second, the article clarifies how educational dark tourism has developed in the case of the Fukushima Hope Tourism Guided Tour.